Soil fertility status under different land uses and its management practices in Bure district of Ilu Ababor zone, southwest Ethiopia - Tadesse, Solomon; Assefa, Tekalign (Brawijaya University, 2024)
The study examined soil fertility status under different land use types and its management practices in Bure district of Illubabor zone, southwest Ethiopia. A structured questionnaire survey of 546 randomly selected smallholder farmers was employed to collect data, along with focus group discussions, key informant interviews, and personal observations. In addition, thirty-two composite soil samples were taken at a depth of 0-30 cm from forest, grazing, and cultivated lands to determine soil fertility status. The data were analyzed using ANOVA and descriptive statistics. The findings of the soil analysis showed that the distribution of soil particle sizes, available phosphorus, total nitrogen, soil organic carbon, organic matter, and cation exchange capacity varied significantly (p<0.05) between forest, grazing, and cultivated lands. The findings also showed that when land use and cover shifted from forests to cultivated and grazing lands, soil fertility decreased. The pH of the soil under cultivated land was found to be highly acidic, while the soil under forest and grazing lands was found to be strongly acidic. The most widely used soil fertility management practices were the application of miner fertilizer, building of bunds, planting of vetiver grass, contour plowing, crop rotation, straw and mulching, and agroforestry practices. The findings of this study suggest that in highly acidic soils found in cultivated lands, applying an adequate amount of lime can help to enhance soil fertility and boost land productivity.